2021
DOI: 10.23844/kjcp.2021.02.33.1.539
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Sex Discrimination and Job and Life satisfaction in Female Employees: The Mediating Effects of Work Volition and Decent Work

Abstract: This study aimed to apply psychology of working theory, and identify the mediating effects of work volition and decent work on the association between sex discrimination and job and life satisfaction in women. A total of 350 female employees completed the questionnaires, and data from 301 participants were analysed using SPSS 18.0 and AMOS 18.0. The results indicated that sex discrimination had a negative effect on work volition, and work volition had positive effect on decent work. However, the effect of sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Previous applications of PWT in Korea directly predicted job satisfaction, but not life satisfaction (Lee and Lee, 2020 ). Elsewhere, Duffy et al ( 2019 ) reported that decent work had a direct, significant effect on the physical health of American workers, but not on their mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous applications of PWT in Korea directly predicted job satisfaction, but not life satisfaction (Lee and Lee, 2020 ). Elsewhere, Duffy et al ( 2019 ) reported that decent work had a direct, significant effect on the physical health of American workers, but not on their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…While the PWT has been intensely studied abroad, it has only recently become a topic of interest in Korea. Reports available from Korea verified that structural constraints (social class and gender discrimination) negatively affected working people, women, and college students (Ahn, 2019 ; Kim et al, 2019 ; Lee and Lee, 2020 ). Additionally, a study validated the DWS for use in Korean working adults (Nam and Kim, 2019 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%